Role of diabetes in stroke: Recent advances in pathophysiology and clinical management. Issue 2 (23rd September 2021) - Bradley, Sian A.; Spring, Kevin J.; Beran, Roy G.; Chatzis, Dimitrios; Killingsworth, Murray C.; Bhaskar, Sonu M. M.
Abstract: The increasing prevalence of diabetes and stroke is a major global public health concern. Specifically, acute stroke patients, with pre‐existing diabetes, pose a clinical challenge. It is established that diabetes is associated with a worse prognosis after acute stroke and the various biological factors that mediate poor recovery profiles in diabetic patients is unknown. The level of association and impact of diabetes, in the setting of reperfusion therapy, is yet to be determined. This article presents a comprehensive overview of the current knowledge of the role of diabetes in stroke, therapeutic strategies for primary and secondary prevention of cardiovascular disease and/or stroke in diabetes, and various therapeutic considerations that may apply during pre‐stroke, acute, sub‐acute and post‐stroke stages. The early diagnosis of diabetes as a comorbidity for stroke, as well as tailored post‐stroke management of diabetes, is pivotal to our efforts to limit the burden. Increasing awareness and involvement of neurologists in the management of diabetes and other cardiovascular risk factors is desirable towards improving stroke prevention and efficacy of reperfusion therapy in acute stroke patients with diabetes.